Physiological and training characteristics of recreational marathon runners - Gordon D; Wightman S; Basevitch I; Johnstone J; Espejo-Sanchez C; Beckford C; Boal M; Scruton A; Ferrandino M; Merzbach V (Dove Medical Press, 2017)
Dan Gordon,1 Sarah Wightman,2 Itay Basevitch,1 James Johnstone,1 Carolina Espejo-Sanchez,1 Chelsea Beckford,1 Mariette Boal,1 Adrian Scruton,1 Mike Ferrandino,1 Viviane Merzbach1 1Cambridge Centre for Sport and Exercise Sciences, Anglia Ruskin University, 2The Flying Runner, Cambridge, UK Purpose: The aim of this study was to examine the physical and training characteristics of recreational marathon runners within finish time bandings (2.5–3 h, 3–3.5 h, 3.5–4 h, 4–4.5 h and >4.5 h).Materials and methods: A total of 97 recreational marathon runners (age 42.4 ± 9.9 years; mass 69.2 ± 11.3 kg; stature 172.8 ± 9.1 cm), with a marathon finish time of 229.1 ± 48.7 min, of whom n = 34 were female and n = 63 were male, completed an incremental treadmill test for the determination of lactate threshold (LT1), lactate turn point (LT2) and running economy (RE). Following a 7-min recovery, they completed a test to volitional exhaustion starting at LT2 for the assessment of VO2max. In addition, all participants completed a questionnaire gathering information on their current training regimes exploring weekly distances, training frequencies, types of sessions, longest run in a week, with estimations of training speed, and load and volume derived from these data.Results: Training frequency was shown to be significantly greater for the 2.5–3 h group compared to the 3.5–4 h runners (P < 0.001) and >4.5 h group (P = 0.004), while distance per session (km⋅session–1) was significantly greater for the 2.5–3 h group (16.1 ± 4.2) compared to the 3.5–4 h group (15.5 ± 5.2; P = 0.01) and >4.5 h group (10.3 ± 2.6; P = 0.001). Race speed correlated with LT1 (r = 0.791), LT2 (r = 0.721) and distance per session (r = 0.563).Conclusion: The data highlight profound differences for key components of marathon running (VO2max, LT1, LT2, RE and % VO2max) within a group of recreational runners with the discriminating training variables being training frequency and the absolute training speed. Keywords: endurance running, nonelite, workout structures, maximal oxygen uptake, running economy, aerobic capacity